Delayed diagnosis and surgical management of gastric perforation: a case report - Gonidjaya, Joshua J. (International Surgery Journal, 2025)
Gastric perforation is a life-threatening emergency requiring prompt diagnosis and intervention. However, in resource-limited settings, delayed diagnosis and referral can worsen outcomes. This report presents a case of gastric perforation initially misdiagnosed as perforated appendicitis, leading to delayed treatment and increased morbidity. A 56-year-old male presented with severe, diffuse abdominal pain for one day, accompanied by the inability to pass stool and urine. The patient had a history of chronic knee pain and frequent NSAID and corticosteroid use. He was initially misdiagnosed at a rural hospital due to the unavailability of imaging and referred to a primary hospital with X-ray facilities after a two-day delay. On arrival, he showed signs of sepsis and peritonitis. Abdominal X-ray revealed free air under the diaphragm, confirming gastric perforation. Emergency laparotomy showed a 1×1 cm gastric perforation with extensive peritoneal contamination and omental inflammation. Primary closure with omental patch repair was performed, followed by peritoneal lavage. The patient was managed in the intensive care unit (ICU) for three days before transferring to the general ward. He was discharged after ten days with weekly follow-ups for one month. This case highlights the challenges of diagnosing gastric perforation in resource-limited settings and emphasizes the need for improved access to imaging and timely surgical intervention. Delayed diagnosis increases morbidity, underscoring the importance of efficient referral systems and early detection.